'Red Fury': Historical memory and Spanish football. (October 2014) - Camino, Mercedes
Known affectionately as 'La Roja' ('The Red One'), the Spanish national football team has had a trajectory that is inextricably linked with the country's historical and political events. The 'historical memory' of this convoluted historical period also infuses the history of the sport itself in Spain and is thoroughly marked by the authoritarian regime that governed the country at the time (1939–1975). This is a history that is indelibly marked by the military coup led by Francisco Franco and the dictatorship that followed it, which remain contested ground in twenty-first-century Spain. It is this historical amalgamation, this article will argue, that makes Spanish football an exemplary arena from which to observe the processes of memorialising and coming to terms with a divisive past.